Mowa nienawiści w wybranych orzeczeniach niemieckich sądów w kontekście wybranych orzeczeń polskich sądów - Patora, Krystyna (Problemy Prawa Karnego, 2024)
The article focuses on selected rulings of German courts that deal with behaviour defined in the German Criminal Code as the crime of incitement to popular hatred. The purpose of this article is to present how courts have assessed specific statements from the point of view of the occurrence of prohibited acts characteristics in hate speech. The article presents the facts and legal evaluation of the behaviour to indicate which behaviors fulfill the characteristics of the criminal act of inciting to popular hatred under German laws. Also selected rulings of Polish courts, which relate to the interpretation of the characteristics of the hate speech crime, are taken into consideration. The author has selected some rulings of Polish courts, which are thematically similar to the rulings of German courts. In conclusion, the author has pointed out the differences between the characteristics of criminal acts in German laws and Polish laws, and thus a different approach of two judicial systems to some specifically indicated contents.